PDF The Necessity of Walking in the Light: An Exegesis of 1 John 1:5-10 (Impact: Journal of Transformation, 2023)
1 John 1:5-10 is an exhortatory piece whose subject is the character of Christian living in relationto God’s standard of holiness. This paper is a study of the necessity of walking in the light basedon the exegesis of 1 John 1:5-10. The exegesis applies the grammatical-historical methodthrough which the researcher examines the grammar, syntax, and the literary structure of 1 John1:5-10. The statement, ὁ θεὸς φῶς ἐστιν καὶ σκοτία ἐν αὐτῷ οὐκ ἔστιν οὐδεμία, in verse 5 and itsrelated concepts in the other verses serves as the central idea under investigation. The researcherobserves that the author uses a pastoral rhetoric method to warn against three negative claimsand practices (1 Jn 1:6, 8, 10) and encourages his audience to observe two positive confessionsand practices (1 Jn 1:7, 9), all of which are related to verse 5. The exegesis shows that the aim ofthe author is to encourage believers to live according to the fact that God is light and requiresthat those who have fellowship with him should walk in the light (1 Jn 1:5-7). This article hashighlighted some of the ways in which Christians today can be motivated to pursue a holy life asa requirement by God in order to conform to his nature.